Liver and plasma lipid changes induced by cyclic fatty acid monomers from heated vegetable oil in the rat. Issue 8 (16th October 2018) - Mboma, Jean; Leblanc, Nadine; Wan, Sereana; Jacobs, René L.; Tchernof, André; Dubé, Pascal; Angers, Paul; Jacques, Hélène
Abstract: Cyclic fatty acid monomers (CFAM) generated through domestic or industrial heating of vegetable oils may alter liver enzymes and induce hepatomegaly and steatosis, but the underlying mechanisms are not clearly understood. This study aimed to assess the effects of CFAM on liver and plasma lipids and to determine whether these effects are modulated by dietary lipids. Thirty‐six (36) male Wistar rats were fed either of the four isoenergetic diets consisting of canola oil or soybean oil with/without 500 mg/100 g CFAM of total fat for 28 days. Rats fed CFAM had higher liver total lipids ( p = 0.03) and triacylglycerols (TAG) ( p = 0.02), but less hepatic phosphatidylcholine ( p = 0.02) compared to those fed the non‐CFAM diets. CFAM did not alter liver phosphatidylethanolamine N ‐methyltransferase (PEMT) activity and CTP: phosphocholine cytidylyltransferase (CT‐α) protein levels. Rats fed CFAM diets had higher levels of plasma total cholesterol (TC), VLDL + LDL cholesterol, higher ratio of TC to HDL cholesterol, and lower levels of HDL cholesterol compared with rats fed non‐CFAM diets ( p < 0.05). Plasma alanine transaminase (ALT) was decreased with CFAM, but plasma insulin, glucose, and TAG did not vary among the four diet groups ( p < 0.05). Rats fed canola oil and CFAM had higher plasma levels of aspartate transaminase (AST) and AST/ALT ratio compared with the other three diet groups. These results indicate that CFAM may provoke an accumulation of TAG in the liver related to a decrease in phosphatidylcholine (PC) levels, but the effect of CFAM on PC concentrations may not occur through impairment of the two main PC biosynthesis pathways. Abstract : Cyclic fatty acid monomers from heated vegetable oils induce high triacylglycerol content and decrease in phosphatidylcholine in the liver of rats. The high correlation between the two events suggests a possible mechanistic explanation.